A 2060MPa grade high-strength multiphase hot-rolled wire rod for bridge cables and a manufacturing method thereof

Through the C-Si-Mn-Cr-V component design and online molten salt semi-quenching treatment technology, the problems of high-strength hot-rolled strips in the existing technology have strong process sensitivity and difficulty in stable production on Steyrmo air-cooled lines, and controllable regulation of compound phase structure and high-strength and good plasticity hot-rolled strips are achieved, which are suitable for the stable production of 2060MPa-level bridge cables.

CN119162429BActive Publication Date: 2025-03-28JIANGSU YONGGANG GROUP CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411650082.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-03-28
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

The prior art is difficult to produce high-strength hot-rolled strips for 2060MPa-level bridge cables at high quality and stable production on Steyrmo air-cooled lines, which are mainly due to the formation of abnormal structures of network carbides and martensite caused by carbon elements, which affects the strength and plasticity of the strips.

Method used

The high-strength composite hot-rolled disk strip designed with C-Si-Mn-Cr-V component is designed. Through the online molten salt semi-quenching treatment technology, it quickly enters the bainite phase region from the high-temperature austenite state, forming a structure dominated by bainite and untransformed austenite. The soxunite transformation is promoted through isothermal treatment of the molten salt in the later stage, reducing tissue stress and dislocation density, and improving the strong plastic matching of the disk strips.

Benefits of technology

It effectively avoids the formation of abnormal tissues such as mesh carbides and martensite, realizes controllable regulation of complex phase structure, improves the strength and plasticity of the strips, and ensures high-quality and stable production of 2060MPa-level bridge cables.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119162429B_ABST
    Figure CN119162429B_ABST
Patent Text Reader

Abstract

The invention relates to a high-strength multi-phase hot-rolled wire rod for 2060MPa-level bridge cables and a manufacturing method thereof. After rolling and spinning into a wire rod with C-Si-Mn-Cr-V components, the wire rod is subjected to an online molten salt semi-quenching treatment, so that the wire rod first passes through a front-stage molten salt and is cooled at a cooling rate of ≥39°C / s, enters a bainite phase region from an austenite state, promotes transformation of a part of austenite to bainite, then undergoes a rear-stage molten salt heating isothermal treatment, promotes transformation of untransformed austenite to bainite, promotes isothermal tempering of the wire rod structure, and finally undergoes roller slow cooling to obtain a hot-rolled wire rod having a microstructure mainly composed of tempered bainite and tempered bainite and a multi-phase structure composed of the rest of micro-spheroidized carbides. The invention can realize controllable regulation of the multi-phase structure, matching of high strength and good plasticity, and stable production, achieve a tensile strength of 1470-1520MPa, and a cross-sectional shrinkage of 39%-44%, and is suitable for stable production and manufacturing of 2060MPa-level bridge cables.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hot-rolled wire rods, and specifically relates to a high-strength multi-phase hot-rolled wire rod for 2060MPa-grade bridge cables and a manufacturing method thereof. Background Art

[0002] Bridge cables are used to connect bridge towers and bridge decks, support the weight of the entire bridge, and ensure the stability and safety of the bridge. The improvement of the strength grade of bridge cables is conducive to reducing the amount of steel used in the main cable, while reducing wind resistance during use and improving the stability and safety of the bridge. With the increasing demand for the construction of large-span bridges, the strength grade of bridge cables used in large-span bridges has been continuously improved to 2060MPa, and the improvement of the strength grade of bridge cables also means that the demand for the strength grade of their parent material hot-rolled wire rods has been further improved. At present, for the hot-rolled wire rods of 2060MPa ultra-high strength bridge cables, due to the combined effects of high C content and alloy strengthening, the hot-rolled wire rods are extremely sensitive to the process on the existing Stelmor air-cooling line, and are prone to produce abnormal structures such as high-grade network carbides and martensite, making it extremely difficult to produce high-quality and stable production. Therefore, it is an urgent problem to develop a 2060MPa hot-rolled wire rod for bridge cables with higher strength grade and high-quality and stable production to meet the development of the steel industry and market demand.

[0003] The causes and technical difficulties that limit the high-quality and stable production of 2060MPa grade high-strength hot-rolled wire rods for bridge cables in the prior art are: 1. Carbon, as a carbide strengthening element and austenite forming element, has a high content in high-strength hot-rolled wire rods, but it also increases the risk of carbon segregation and precipitation of network cementite during the solidification of the steel billet. At the same time, due to the cooling capacity of the Stelmor air-cooling line, the wire rod passes through a long temperature interval for the precipitation of secondary cementite, so the cementite precipitated along the grain boundary will aggregate into a network precipitation. The network carbide will not only destroy the continuity between the lattices and increase the fluctuation of mechanical properties, but also And it will seriously deteriorate the plastic toughness of the wire rod, which will cause wire breakage or torsion failure during the manufacturing of bridge cables. In order to minimize the level of network carbides, the existing technology will increase the air volume of the fan after spinning. For example, patent CN112391584A discloses a 2060MPa grade bridge cable steel wire heat-treated wire rod, which adopts C-Si-Mn-Cr-V-Al component design combined with low-temperature rolling and spinning, first fast and then slow cooling, and then heating isothermal salt bath treatment to obtain a troostite structure wire rod; or patent CN114657471B discloses a ≥2060MPa grade The wire rod for bridge cables adopts C-Si-Mn-Cr-B-Al composition design combined with Stelmor air cooling + mist cooling after spinning to obtain troostite wire rod; however, on the one hand, the maximum cooling rate of the wire rod after strong air cooling or combined with mist cooling is still limited, and the improvement effect on the network carbide is limited. Further offline treatment such as austenitizing heating and isothermal salt bath will further increase the production process, time consumption, energy consumption and cost; on the other hand, in order to make it easier to obtain pearlite or troostite structure with fine lamellar spacing at a lower phase transformation temperature during wire rod controlled cooling, the hardenability of Mn, Cr and other materials in the wire rod is increased. The element content is high, but it also intensifies the segregation of alloy elements. With the increase of wind cooling intensity, the temperature difference between the windward side and the leeward side of the wire rod, and the overlap and non-overlap parts further increases. Or a large number of bubbles are generated due to water cooling and adhere to the surface of the wire rod, affecting heat transfer and increasing the temperature difference. Under the influence of strengthening the segregation of alloy elements, the supercooled position is more likely to form abnormal hard and brittle bainite or martensite structure, which significantly increases the brittleness of the wire rod, affects the drawing ability of the wire rod, limits the stable production of the wire rod, and may cause brittle fracture of the wire rod during unwinding, drawing or torsion of the downstream users. Offline heat treatment also has the problem of increased procedures and costs.

[0004] Second, in order to improve the strength and drawing performance of the wire rod as much as possible, although the air cooling intensity is reduced in the temperature range close to the phase change to prolong the phase change time to increase the troostite conversion rate, and trace alloying elements such as V and B are added for strengthening, on the one hand, limited by the minimum cooling capacity of Stelmor air cooling or insulation or combined with water cooling, the phase change incubation time in the continuous cooling process is limited, which will limit the further increase of the troostite content and the large-scale dispersion and precipitation of strengthening carbides, affecting the role of strengthening elements and the further improvement of the wire rod strength. If the low-temperature brittle element with uncontrollable transformation is doped Although the abnormal organization can improve the strength, the transformation is uncontrollable, it is difficult to produce stably and will sharply deteriorate the plasticity of the wire rod, resulting in coiling or drawing fracture; on the other hand, limited by the continuous cooling of the Stelmor wire, the thickness of the cementite layer is large during phase transformation and the temperature is relatively low after the phase transformation incubation, which increases the difficulty of softening, resulting in large residual stress in the wire rod organization. The dislocation density of the resulting troostite organization is high, and it is difficult to obtain good plasticity matching the high strength. The hot-rolled wire rod is obviously hardened during drawing, and the plasticity will be lost quickly during subsequent drawing, which will cause wire breakage or torsion failure. Summary of the invention

[0005] The present invention aims to solve at least one of the above-mentioned technical problems to a certain extent. The present invention provides a high-strength complex phase hot-rolled wire rod for 2060MPa grade bridge cables and a manufacturing method thereof, which can achieve controllable regulation of complex phase structure, matching of high strength and good plasticity, and stable production, and is suitable for the stable production of 2060MPa grade bridge cables.

[0006] The technical solution adopted by the present invention to solve its technical problem is:

[0007] A method for manufacturing a 2060MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables, the manufacturing method comprising:

[0008] The wire rod is produced by rolling according to the chemical composition of the hot-rolled wire rod, wherein the chemical composition and mass percentage of the hot-rolled wire rod include: C: 0.87%~0.91%, Si: 0.70%~0.85%, Mn: 0.50%~0.70%, Cr: 0.35%~0.45%, V: 0.035%~0.045%, P≤0.015%, S≤0.015%, and the rest are Fe and unavoidable impurities; the wire rod is spun at a spinning temperature of ≥915°C. After the wire rod is formed, it is subjected to online molten salt semi-quenching treatment, so that the wire rod first passes through the front section of molten salt and is cooled at a cooling rate of ≥39°C / s, enters the bainite phase region from the austenite state, promotes the transformation of part of the austenite to bainite, and then undergoes the rear section of molten salt heating isothermal treatment to promote the transformation of the untransformed austenite to bainite, promotes the isothermal tempering of the wire rod structure, and finally passes through roller slow cooling to obtain a hot-rolled wire rod with a microstructure mainly composed of tempered bainite and tempered bainite, and the rest of the microspheroidized carbides forming a complex phase structure.

[0009] The design basis of the chemical composition and mass percentage of the above hot rolled wire rod includes:

[0010] (1) Carbon: As the main and effective strengthening element in steel, C can play a role in solid solution strengthening and carbide precipitation strengthening. At the same time, it is cheaper than other alloying elements. With the increase of carbon content, it is conducive to the formation of more cementite lamellae in the wire rod during the controlled cooling process, and cooperates with precipitation strengthening to improve the tensile strength of the material. However, with the increase of carbon content in hypereutectoid steel, the composition segregation will be aggravated during the solidification process of the alloy, increasing the tendency of decarburization and secondary cementite precipitation, and the difficulty of softening the mixed structure of bainite and troostite, which will deteriorate the toughness and plasticity of the material and affect the cross-sectional shrinkage rate, drawing and torsion properties of the wire rod. Therefore, in order to take into account the high strength requirements of 2060MPa grade bridge cables, reduce the difficulty of controlling network carbides, and reduce the difficulty of isothermal softening of wire rod structures, the mass percentage of C is controlled to be 0.87%~0.91%.

[0011] (2) Silicon: The Si element is often used as a deoxidizer during the smelting process. It also has a high solid solution strengthening ability. It can inhibit the coarsening of cementite during the previous molten salt treatment and accelerate the diffusion rate of carbon, which is beneficial to reduce the difficulty of isothermal tempering softening of bainite and troostite. After the wire rod is drawn into steel wire, it can reduce the strength loss in the subsequent hot-dip galvanizing process. However, too high a silicon content will make the steel more susceptible to decarburization when heated at high temperatures, prolong the transformation time during the phase change process, and reduce the toughness of the steel. Therefore, the mass percentage of Si is controlled to be 0.70%~0.85%.

[0012] (3) Manganese: Mn can be added as a deoxidizer during the smelting process, which can increase the hardenability of the wire rod and the stability of austenite, reduce the phase transition temperature, and thus promote the rapid transformation of some high-temperature austenite to bainite during online molten salt semi-quenching treatment. It can improve the matrix strength through solid solution strengthening. However, if the Mn content is too high, it will increase the overheating sensitivity, grain coarsening and component segregation tendency of the steel, and at the same time reduce the diffusion activity of carbon, which is not conducive to promoting the isothermal tempering softening of the wire rod structure during the subsequent molten salt treatment, thereby losing the plasticity of the wire rod. Therefore, in order to take into account the high strength of the hot-rolled wire rod and facilitate the control of the complex phase structure, the mass percentage of Mn is controlled to be 0.50%~0.70%.

[0013] (4) Chromium: Cr is a medium-strong carbide-forming element in high carbon steel. It can improve the stability of austenite and the hardenability of wire rod, promote the bainite phase transformation during the front-end molten salt treatment, and improve the matrix strength by forming compound precipitation, shifting the steel C curve to the right, and promoting the refinement of troostite lamellae. At the same time, it can reduce the strength loss of wire rod during hot-dip galvanizing after drawing. However, too high Cr content will aggravate component segregation, reduce the activity of carbon in steel, and be unfavorable for isothermal softening during the back-end molten salt treatment, which significantly increases the difficulty of improving the plasticity of wire rod. Therefore, the mass percentage of Cr is controlled to be 0.35%~0.45%.

[0014] (5) Vanadium: As a strong carbide-forming element, V can be dispersed and precipitated in large quantities in the medium temperature range of 500~600℃, which can refine the grains and strengthen the precipitation, increase the matrix strength, and provide hydrogen traps to improve the hydrogen embrittlement resistance of the wire rod. However, since V is expensive, excessive addition will lead to an increase in the cost of the wire rod. Therefore, the mass percentage of V is controlled to be 0.035%~0.045%.

[0015] (6) Phosphorus and sulfur: P and S are impurity elements. The lower the better. Therefore, P is controlled to be ≤ 0.015% and S is ≤ 0.015%.

[0016] The hot-rolled wire rod adopts C-Si-Mn-Cr-V composition design. The hardenability of the wire rod is regulated by optimizing the composition ratio, which provides favorable conditions for regulating bainite phase transformation, promoting the refinement of troostite lamellae and the precipitation of V-containing carbides at medium temperature, and reducing the difficulty of isothermal tempering softening of the wire rod structure. On this basis, an appropriate spinning temperature is selected to promote the austenitization of the wire rod structure and avoid the formation of network carbides due to too low spinning temperature. At the same time, favorable conditions are provided to increase the temperature gradient and promote the rapid transformation of the wire rod structure into bainite during the front-stage molten salt treatment. The wire rod is directly subjected to online molten salt semi-quenching treatment with molten salt without air cooling:

[0017] 1. Compared with Stelmor air cooling or combined water mist cooling, the maximum cooling capacity is limited or uncontrollable. The manufacturing method can utilize the high heat exchange capacity of molten salt, and because the temperature of the bainite phase is lower than that of the pearlite phase, a larger temperature gradient can be formed. On the one hand, the wire rod is cooled quickly, and the secondary cementite precipitation temperature range of 700-800°C is quickly passed, avoiding the formation of a network carbide structure that degrades the uniformity of the organization and the plasticity of the wire rod due to the influence of carbon segregation, effectively and stably controlling the network carbide and improving the utilization value of the carbon element; on the other hand, The wire rod directly enters the bainite phase region from the high-temperature austenite state, promoting the transformation of part of the high-temperature austenite to the bainite structure, forming a structure mainly composed of bainite and untransformed austenite, which can make the bainite transformation, which is conventionally regarded as an abnormal structure, more controllable, and further improve the matrix strength by forming bainite by quenching. At the same time, compared with air cooling or water mist cooling, the molten salt can cover the surface of the wire rod when the wire rod passes through the molten salt. There is no temperature difference between the windward side and the leeward side, and there is no problem of a large number of bubbles interfering with heat transfer, so that the temperature difference in the same circle of the wire rod is smaller, and the formation of hard and brittle martensite abnormal structure during the processing process can be avoided.

[0018] 2. Compared with the Stelmore air cooling or combined with water mist cooling, which has a limited minimum cooling capacity and continuous cooling treatment, the wire rod can be subjected to the isothermal treatment of molten salt heating in the latter stage after the front stage molten salt quenching. On the one hand, the wire rod can be kept consistent with the molten salt temperature, and the isothermal phase transformation incubation can be carried out for a longer time close to the peak precipitation temperature of the sorbite, which promotes the transformation of the untransformed high-temperature austenite in the wire rod to the sorbite with finer interlamellar spacing after the front stage molten salt treatment, and promotes the precipitation of a large number of fine V-containing carbides in the medium temperature range, further improving the strength of the wire rod, and avoiding the formation of abnormal martensite structure during the subsequent roller slow cooling process due to the residual austenite; on the other hand, the temperature of the bainite phase region after the rear stage molten salt heating is higher than that of the bainite phase region. Higher temperature can provide more thermal power for isothermal tempering softening. As the high-temperature isothermal treatment time is extended, the bainite and troostite structures formed by phase transformation can be softened, the tissue stress and dislocation density can be reduced, and the hard and brittle bainite structure can be transformed into a strong and tough structure, promoting the transformation of carbides to spheroidized structures, improving the plasticity of the wire rod, and making the wire rod structure more uniform. After that, the wire rod passes through the rear molten salt at a higher temperature and then slowly cools down through a roller table, which can prevent the stress of the wire rod from increasing during the cooling process. At the same time, slow cooling can be used to continue the high temperature state of the wire rod, promote further toughening of the wire rod structure, improve the softening effect of the wire rod, and realize the matching of complex phase structure regulation and high-strength and plastic performance.

[0019] Selecting an appropriate heating furnace soaking temperature before rolling can promote uniform diffusion of alloy components, while controlling the time in the furnace to avoid the risk of burning or decarburization caused by too long time in the furnace, in preparation for controlling the rolling temperature. In a preferred embodiment, before rolling, the heating furnace soaking temperature is controlled to be 1100~1150℃, and the time in the furnace is 100~180min.

[0020] Since the spinning temperature is relatively high, the restriction on the rolling temperature can be reduced. The appropriate rolling temperature is selected to reduce the deformation resistance of the rolled piece and control the decarburization of the rolled piece, which is beneficial to improving the rolling speed and efficiency. At the same time, the dynamic recrystallization of the rolled piece during the final rolling process is controlled with an appropriate reduction, the grains are refined, and the matrix is ​​strengthened and toughened. In a preferred embodiment, during the rolling, the initial rolling temperature is controlled to be 1080~1130℃, the final rolling temperature is 935~975℃, and the final rolling reduction is 29%~34%.

[0021] The molten salt temperature of the front stage molten salt is in the bainite phase temperature of the wire rod. The lower the molten salt temperature and the longer the treatment time, the more austenite transforms to bainite, the proportion of tempered bainite in the wire rod increases, the strength of the wire rod increases, and the plasticity decreases. However, if the molten salt temperature is too low and the treatment time is too long, the proportion of tempered bainite in the wire rod is too small, or even abnormal martensite structure is formed due to overcooling, which is not conducive to controlling the plasticity and drawing performance of the wire rod. On the contrary, the higher the molten salt temperature and the shorter the treatment time, the less austenite transforms to bainite, and there is no transformation afterwards. The increase in the transformation of transformed austenite to troostite will lead to a decrease in matrix strength and an increase in plasticity. However, if the molten salt temperature is too high and the treatment time is too short, the bainite phase transformation will be affected, resulting in a loss of matrix strength and even affecting the control of network carbides. Therefore, the molten salt temperature and treatment time of the front-stage molten salt can be controlled to allow the wire rod to form a structure mainly composed of bainite and untransformed austenite, thereby making organizational preparations for the rear-stage molten salt isothermal treatment. In a preferred embodiment, the molten salt temperature of the front-stage molten salt is 420~450℃, and the treatment time is 7~18s.

[0022] Since the temperature gradient between the spinning temperature and the bainite phase region is large, selecting a larger molten salt circulation rate can control the molten salt temperature rise, promote the rapid cooling of the wire rod from the high-temperature austenite state, and promote the rapid quenching and nucleation of bainite. In a preferred embodiment, the molten salt circulation rate of the front-stage molten salt is 560~660t / h, and the molten salt temperature rise is ≤9°C.

[0023] The molten salt temperature of the rear-stage molten salt is higher than that of the front-stage molten salt. The lower the molten salt temperature of the rear-stage molten salt, the more beneficial it is to promote the transformation of the untransformed austenite structure to the troostite structure with finer interlamellar spacing, and the dispersion and precipitation of V-containing carbides. However, if the molten salt temperature is too low, it is difficult to provide more thermal power for isothermal softening, which will lead to insufficient plasticity of the wire rod, and even affect the precipitation of V-containing carbides due to too low temperature, lower than the medium temperature. On the contrary, the higher the molten salt temperature, the more thermal power can be provided for the isothermal softening and toughening of bainite and troostite, promote the transformation of carbides to spheroidization, and improve the plasticity of the wire rod. However, if the molten salt temperature is too high, it is not conducive to the refinement of the troostite lamellae and the large-scale precipitation of V-containing carbides in the crystal, which will lose the strength of the wire rod. The longer the treatment time, the The austenite is fully transformed into the troostite, and the isothermal softening effect is improved at the same time, and the plasticity and toughness of the wire rod are better. However, if the treatment time is too long, there is a risk of excessive loss of strength, coarsening of carbides or spheroidization aggregation and growth, and loss of strength and plasticity. The shorter the treatment time, the lower the softening effect and the plasticity of the wire rod. However, if the treatment time is too short, the troostite is not fully transformed, and the V-containing carbides have no time to precipitate in large quantities, the tissue stress is high, and the bainite tissue distortion is high, which will obviously lose strength and plasticity. Therefore, the molten salt temperature and treatment time of the rear-stage molten salt can be further controlled to adjust the wire rod structure and improve the strength and plasticity matching of the wire rod. In a preferred embodiment, the molten salt temperature of the rear-stage molten salt is 550~590℃, and the treatment time is 400~600s.

[0024] Selecting an appropriate molten salt circulation rate in the rear-stage molten salt can further control the temperature accuracy of the molten salt, promote uniform tissue transformation, and avoid unnecessary increase in production energy consumption due to excessive molten salt circulation rate. In a preferred embodiment, the molten salt circulation rate of the rear-stage molten salt is 350~450t / h, and the molten salt temperature rise is ≤3°C.

[0025] In a preferred embodiment, the roller slow cooling controls the wire rod to be slowly cooled at a cooling rate of 0.3-0.5°C / s above 350°C, which can promote further toughening of the wire rod structure and improve the softening effect of the wire rod.

[0026] In a preferred embodiment, the roller slow cooling adopts an open insulation cover, and the wire rod is transported by the roller into the insulation cover, which can use its own waste heat to slowly cool down and reduce production energy consumption.

[0027] A 2060MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables, wherein the hot-rolled wire rod is manufactured by any of the above-mentioned methods for manufacturing 2060MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables.

[0028] The hot rolled wire rod adopts the hypereutectoid composition design containing trace V elements and the control of the complex phase structure. Compared with the traditional wire rod structure composed of troostite + ferrite for bridge cables, the complex phase structure is mainly tempered troostite and tempered bainite, containing a small amount of spheroidized carbide. Bainite has higher distortion and dislocation density and higher strength than troostite structure. After the bainite phase change is controllable, it is further isothermally transformed into a strong and tough tempered bainite structure at high temperature. The high strength characteristics of bainite, which is conventionally regarded as an abnormal structure, can be utilized. Points, combined with the dispersion and precipitation of troostite and V-containing carbides, further improve the matrix strength. Compared with pearlite, the troostite has finer interlamellar spacing, better strength and drawing properties, and better plasticity than bainite. Troostite transforms to tempered troostite after high temperature isothermal treatment, and carbides transform from spheroidized structure to micro-spheroidized carbides. The organizational stress and dislocation density are further reduced. The plasticity of the wire rod is comprehensively improved through the organizational regulation of the tempered state, thereby achieving higher strength of the hot-rolled wire rod while having good plasticity.

[0029] The finer the interlamellar spacing of the tempered troostite is, the more beneficial it is to improving the matrix strength and the drawing hardening ability. In a preferred embodiment, the interlamellar spacing of the tempered troostite is 70-130 mm, and the volume percentage of micro-spheroidized carbides is ≥2%.

[0030] The higher the proportion of the tempered bainite in the multiphase structure, the more beneficial it is to improving the matrix strength. In a preferred embodiment, the volume percentage of the tempered bainite is 55% to 65%.

[0031] In a preferred embodiment, the network carbide grade of the hot-rolled wire rod is level 0, which can reduce the adverse effects of the network carbide on the uniformity of the structure and the plasticity of the wire rod, and facilitate the high-quality and stable production of the hot-rolled wire rod and bridge cables.

[0032] The network carbide and martensite abnormal structures of the hot-rolled wire rod are effectively controlled, and the complex phase structure is evenly distributed, which can further reduce the fluctuation of the mechanical properties of the wire rod and is beneficial to reducing the risks of wire breakage during drawing and torsion failure. In a preferred embodiment, the mechanical property difference of the hot-rolled wire rod is ≤52MPa.

[0033] In a preferred embodiment, the diameter of the hot-rolled wire rod is 11.0~15.0mm, the tensile strength is 1470~1520MPa, and the cross-sectional shrinkage rate is 39%~44%. The wire rod has a high tensile strength, which is convenient for reaching the performance level faster after drawing, and compensates for the strength loss in the hot-dip galvanizing process of bridge cable manufacturing. At the same time, the wire rod has a high cross-sectional shrinkage rate, which manifests as good deformation ability, and can reduce the risk of wire breakage and torsional fracture during deep drawing and surface reduction.

[0034] Compared with the prior art, the beneficial effects of the present invention are at least:

[0035] (1) Aiming at the current situation that the existing 2060MPa ultra-high strength bridge cables are extremely sensitive to process and difficult to produce stably on the existing Stelmor air-cooling line, the present invention controls the wire rod to quickly enter the bainite phase region from the high-temperature austenite state by designing the C-Si-Mn-Cr-V chemical composition combined with the online molten salt semi-quenching technology, so as to form a structure mainly composed of bainite and untransformed austenite, making the bainite phase change more controllable, and then heating up to promote the transformation of untransformed austenite into troostite, while promoting the high-temperature isothermal treatment of the wire rod structure, improving the strength-plasticity matching of the wire rod, and finally slow cooling through rollers to prevent the wire rod from increasing stress during the cooling process, and promote further toughening of the wire rod structure, thereby improving the softening effect of the wire rod, which can effectively avoid abnormal structures such as network carbides and martensite, realize complex phase structure regulation, reduce mechanical property fluctuations, and facilitate stable production. At the same time, compared with offline heat treatment, the present invention has fewer steps, shorter time consumption, and higher efficiency, and has good industrial adaptability.

[0036] (2) Aiming at the problems of insufficient strength and plasticity, difficult to control abnormal structures and large fluctuations in mechanical properties of existing 2060MPa ultra-high strength bridge cables, the hot-rolled wire rod microstructure type of the present invention includes a complex phase structure composed mainly of tempered bainite and tempered bainite, and a small amount of micro-spheroidized carbides, which can effectively reduce the adverse effects of abnormal structures such as network carbides and martensite on the uniformity of the structure and the plasticity of the wire rod, and transform the bainite into tempered bainite that is both strong and tough. The matrix strength is further improved by the large-scale dispersion and precipitation of tempered bainite and V-containing carbides. The structure stress and dislocation density are further reduced through the organization regulation of the tempered state, and the plasticity of the wire rod is comprehensively improved, which is more convenient for stable production. At the same time, the tensile strength can reach 1470~1520MPa and the cross-sectional shrinkage rate can reach 39%~44%. It is used in the manufacture of 2060MPa ultra-high strength bridge cables and other application fields, and has good market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0038] Figure 1 is a metallographic structure diagram of Example 1 of the present invention;

[0039] Figure 2 is the metallographic structure diagram of Example 2 of the present invention;

[0040] Figure 3 It is the metallographic structure diagram of Example 3 of the present invention. DETAILED DESCRIPTION

[0041] The embodiments described below with reference to the accompanying drawings are exemplary and are only for illustration and do not limit the description of the features and characteristics of the present invention, so as to propose the best way to implement the present invention, and are intended to be used to explain the present invention and are sufficient to enable those skilled in the art to implement the present invention, but cannot be understood as any limitation on the scope of the present invention, which is limited only by the appended claims; the organization and performance testing of the hot-rolled wire rods obtained in the following embodiments and comparative examples include: the tensile test is carried out using "GB-T 228.1-2021 Metallic Material Tensile Test Part 1: Room Temperature Test Method" to obtain the tensile strength and cross-sectional reduction rate; the organization test is carried out according to the metal microstructure detection method of GB / T13298 standard; the mechanical property same circle difference test method: take 2 circles of wire rod 5m away from the end of the coil, take the overlap area position as the base point, divide each circle of wire rod into 8 sections on average, take 1 tensile specimen on each section, and the strength extreme difference of the tensile specimen after the tensile test is the mechanical property same circle difference. Embodiment 1:

[0042] A preferred embodiment of the 2060MPa grade high-strength multiphase hot-rolled wire rod for bridge cables of the present invention, the chemical composition and mass percentage of the hot-rolled wire rod include C: 0.89%, Si: 0.7%, Mn: 0.53%, Cr: 0.38%, V: 0.037%, P: 0.013%, S: 0.012%, and the rest are Fe and unavoidable impurities; the manufacturing method thereof is manufactured according to the process flow of rolling → spinning → online molten salt semi-quenching treatment → roller slow cooling → coiling, specifically:

[0043] The rolling process is used to heat a steel billet with a specification of 220mm×220mm through a heating furnace to obtain a high-temperature steel billet that can be rolled into plasticity. The parameters of the heating furnace are controlled to promote uniform diffusion of components in the steel billet, reduce segregation, and control burning and decarburization. After the steel billet leaves the heating furnace, the steel billet is rolled into a wire with a diameter of 11mm through a rolling line. Appropriate rolling temperature and deformation are selected to improve the rolling speed and efficiency, promote dynamic recrystallization and refine grains during the final rolling process. Specifically: the heating furnace is controlled to have a soaking temperature of 1100°C. The furnace time is 180min, the initial rolling temperature is 1080℃, the final rolling temperature is 935℃, and the final rolling reduction is 29%; the wire-spinning process is used to make the wire rod out of the rolling line into a wire rod through a wire-spinning mechanism, and the wire rod is spread on the roller and transported along the roller. An appropriate wire-spinning temperature is selected to promote the wire rod to be in a high-temperature austenite state, and to avoid the formation of network carbides in the wire-spinning stage caused by too low a wire-spinning temperature, so as to form a large temperature gradient later, thereby providing favorable conditions for promoting bainite nucleation. Specifically, the wire-spinning temperature is controlled to be 915℃.

[0044] The online molten salt semi-quenching treatment process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller to pass through the first salt bath tank, i.e., the front molten salt treatment, so that the wire rod is cooled at a cooling rate of 39°C / s, and quickly passes through the network carbide precipitation interval from the high-temperature austenite state to the bainite phase region, inhibiting the formation of network carbides, promoting the phase transformation of part of the high-temperature austenite to bainite, and forming a structure mainly composed of bainite and untransformed austenite. The wire rod coming out of the first salt bath tank is conveyed by a roller to pass through the second salt bath tank, i.e., the rear molten salt heating isothermal treatment. Treatment, promote the transformation of untransformed high-temperature austenite into troostite structure, promote the dispersion and precipitation of large amounts of vanadium-containing carbides, and at the same time subject the wire rod structure to high-temperature isothermal tempering, promote the transformation of carbides into spheroidized structure, and improve the strength-plasticity matching of the wire rod. Specifically: the molten salt temperature of the front-stage molten salt is 441°C, the treatment time is 12s, the molten salt circulation volume is 580t / h, and the molten salt temperature rise is ≤9°C; the molten salt temperature of the rear-stage molten salt is 557°C, the treatment time is 480s, the molten salt circulation volume is 380t / h, and the molten salt temperature rise is ≤3°C.

[0045] The roller slow cooling process adopts an open insulation cover, and the wire rod passing through the second salt bath tank is transported by the conveyor roller into the insulation cover to prevent the wire rod from increasing stress during the cooling process, and promote further toughening of the wire rod structure, thereby improving the softening effect of the wire rod. Specifically: the wire rod is controlled to be slowly cooled at a cooling rate of 0.4°C / s above 350°C; the coiling process is used to coil the wire rod into a coil through a coiling drum, and the hot-rolled wire rod product is obtained after packaging and storage. Its metallographic structure diagram is as follows Figure 1 shown.

[0046] Comparative Example 1:

[0047] A method for manufacturing a hot-rolled wire rod, the manufacturing method of which is different from that of Example 1 in that: the manufacturing method is manufactured according to the process flow of rolling → spinning → Stelmor air cooling, specifically: the heating furnace soaking temperature is controlled to be 1040°C, the furnace time is 240min, the initial rolling temperature is 1010°C, the final rolling temperature is 885°C, and the spinning temperature is 855°C; the Stelmor strong air cooling adopts an air volume of 260,000 m per fan 3 / h, open 1~5# fans at 95%, cool the wire rod to 665℃ at a cooling rate of 9.6℃ / s, and then open 6~14# fans at 25%, cool the wire rod to 305℃ at a cooling rate of 2.7℃ / s, and obtain the hot-rolled wire rod product after it comes off the line.

[0048] Comparative Example 2:

[0049] A method for manufacturing a hot-rolled wire rod, which differs from Example 1 in that: the heating furnace soaking temperature is controlled to be 1085°C, the furnace time is 200min, the initial rolling temperature is 1055°C, the final rolling temperature is 910°C, and the spinning temperature is 885°C; after the front-stage molten salt treatment, the wire rod is cooled at a cooling rate of 35°C / s, and the hot-rolled wire rod finished product is obtained after it is off the line. Embodiment 2:

[0050] A preferred embodiment of the 2060MPa grade high-strength multiphase hot-rolled wire rod for bridge cables of the present invention, the chemical composition and mass percentage of the hot-rolled wire rod include C: 0.88%, Si: 0.85%, Mn: 0.5%, Cr: 0.35%, V: 0.042%, P: 0.015%, S: 0.015%, and the rest are Fe and unavoidable impurities; the manufacturing method thereof is manufactured according to the process flow of rolling → spinning → online molten salt semi-quenching treatment → roller slow cooling → coiling, specifically:

[0051] The rolling process is used to heat a steel billet with a specification of 220mm×220mm through a heating furnace to obtain a high-temperature steel billet that can be rolled into plasticity. The parameters of the heating furnace are controlled to promote uniform diffusion of components in the steel billet, reduce segregation, and control burning and decarburization. After the steel billet leaves the heating furnace, the steel billet is rolled into a wire with a diameter of 12mm through a rolling line. Appropriate rolling temperature and deformation are selected to improve the rolling speed and efficiency, promote dynamic recrystallization and refine grains during the final rolling process. Specifically: the heating furnace is controlled to have a soaking temperature of 1115°C The furnace time is 160min, the initial rolling temperature is 1095℃, the final rolling temperature is 945℃, and the final rolling reduction is 31%; the wire-spinning process is used to make the wire rod out of the rolling line into a wire rod through a wire-spinning mechanism, and the wire rod is spread on the roller and transported along the roller. An appropriate wire-spinning temperature is selected to promote the wire rod to be in a high-temperature austenite state, and to avoid the formation of network carbides in the wire-spinning stage caused by too low a wire-spinning temperature, so as to form a large temperature gradient later, thereby providing favorable conditions for promoting bainite nucleation. Specifically, the wire-spinning temperature is controlled to be 920℃.

[0052] The online molten salt semi-quenching treatment process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller to pass through the first salt bath tank, i.e., the front molten salt treatment, so that the wire rod is cooled at a cooling rate of 39°C / s, and quickly passes through the network carbide precipitation interval from the high-temperature austenite state to the bainite phase region, inhibiting the formation of network carbides, promoting the phase transformation of part of the high-temperature austenite to bainite, and forming a structure mainly composed of bainite and untransformed austenite. The wire rod coming out of the first salt bath tank is conveyed by a roller to pass through the second salt bath tank, i.e., the rear molten salt heating, etc. Temperature treatment promotes the transformation of untransformed high-temperature austenite into troostite structure, promotes the dispersion and precipitation of large amounts of vanadium-containing carbides, and at the same time subjects the wire rod structure to high-temperature isothermal tempering to promote the transformation of carbides into spheroidized structure and improve the strength-plasticity matching of the wire rod. Specifically: the molten salt temperature of the front-stage molten salt is 450°C, the processing time is 7s, the molten salt circulation volume is 560t / h, and the molten salt temperature rise is ≤9°C; the molten salt temperature of the rear-stage molten salt is 550°C, the processing time is 480s, the molten salt circulation volume is 350t / h, and the molten salt temperature rise is ≤3°C.

[0053] The roller slow cooling process adopts an open insulation cover, and the wire rod passing through the second salt bath tank is transported by the conveyor roller into the insulation cover to prevent the wire rod from increasing stress during the cooling process, and promote further toughening of the wire rod structure, thereby improving the softening effect of the wire rod. Specifically: the wire rod is controlled to be slowly cooled at a cooling rate of 0.3°C / s above 350°C; the coiling process is used to coil the wire rod into a coil through a coiling drum, and the hot-rolled wire rod product is obtained after packaging and storage. Its metallographic structure diagram is as follows Figure 2 shown.

[0054] Comparative Example 3:

[0055] A method for manufacturing a hot-rolled wire rod, which differs from Example 2 in that the molten salt temperature of the front-stage molten salt is 400°C, the treatment time is 25s, and after the front-stage molten salt treatment, the wire rod is cooled at a cooling rate of 43°C / s, and a hot-rolled wire rod finished product is obtained after it comes off the line.

[0056] Comparative Example 4:

[0057] A method for manufacturing a hot-rolled wire rod, which differs from Example 2 in that the molten salt temperature of the front-stage molten salt is 480°C, the treatment time is 5s, and after the front-stage molten salt treatment, the wire rod is cooled at a cooling rate of 36°C / s, and a hot-rolled wire rod finished product is obtained after it comes off the line. Embodiment 3:

[0058] A preferred embodiment of the 2060MPa grade high-strength multiphase hot-rolled wire rod for bridge cables of the present invention, the chemical composition and mass percentage of the hot-rolled wire rod include C: 0.87%, Si: 0.77%, Mn: 0.55%, Cr: 0.45%, V: 0.045%, P: 0.013%, S: 0.014%, and the rest are Fe and unavoidable impurities; the manufacturing method thereof is manufactured according to the process flow of rolling → spinning → online molten salt semi-quenching treatment → roller slow cooling → coiling, specifically:

[0059] The rolling process is used to heat a steel billet with a specification of 220mm×220mm through a heating furnace to obtain a high-temperature steel billet that can be rolled into plasticity. The parameters of the heating furnace are controlled to promote uniform diffusion of components in the steel billet, reduce segregation, and control burning and decarburization. After the steel billet leaves the heating furnace, it is rolled into a wire with a diameter of 14mm through a rolling line. Appropriate rolling temperature and deformation are selected to improve the rolling speed and efficiency, promote dynamic recrystallization and refine grains during the final rolling process. Specifically: the heating furnace is controlled to have a soaking temperature of 1130°C The furnace time is 120min, the initial rolling temperature is 1110℃, the final rolling temperature is 960℃, and the final rolling reduction is 32%; the wire-spinning process is used to make the wire rod out of the rolling line into a wire rod through a wire-spinning mechanism, and the wire rod is spread on the roller and transported along the roller. An appropriate wire-spinning temperature is selected to promote the wire rod to be in a high-temperature austenite state, and to avoid the formation of network carbides in the wire-spinning stage caused by too low a wire-spinning temperature, so as to form a large temperature gradient later, thereby providing favorable conditions for promoting bainite nucleation. Specifically, the wire-spinning temperature is controlled to be 925℃.

[0060] The online molten salt semi-quenching treatment process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller to pass through the first salt bath tank, i.e., the front molten salt treatment, so that the wire rod is cooled at a cooling rate of 41°C / s, and quickly passes through the network carbide precipitation interval from the high-temperature austenite state to the bainite phase region, inhibiting the formation of network carbides, promoting the phase transformation of part of the high-temperature austenite to bainite, and forming a structure mainly composed of bainite and untransformed austenite. The wire rod coming out of the first salt bath tank is conveyed by a roller to pass through the second salt bath tank, i.e., the rear molten salt heating isothermal treatment. The treatment promotes the transformation of untransformed high-temperature austenite into troostite structure, promotes the dispersion and precipitation of vanadium-containing carbides in large quantities, and at the same time subjects the wire rod structure to high-temperature isothermal tempering to promote the transformation of carbides into spheroidized structure and improve the strength-plasticity matching of the wire rod. Specifically: the molten salt temperature of the front-stage molten salt is 420°C, the treatment time is 18s, the molten salt circulation volume is 630t / h, and the molten salt temperature rise is ≤9°C; the molten salt temperature of the rear-stage molten salt is 590°C, the treatment time is 600s, the molten salt circulation volume is 450t / h, and the molten salt temperature rise is ≤3°C.

[0061] The roller slow cooling process adopts an open insulation cover, and the wire rod passing through the second salt bath tank is transported by the conveyor roller into the insulation cover to prevent the wire rod from increasing stress during the cooling process, and promote further toughening of the wire rod structure, thereby improving the softening effect of the wire rod. Specifically: the wire rod is controlled to be slowly cooled at a cooling rate of 0.5°C / s above 350°C; the coiling process is used to coil the wire rod into a coil through a coiling drum, and the hot-rolled wire rod product is obtained after packaging and storage. Its metallographic structure diagram is as follows Figure 3 shown.

[0062] Comparative Example 5:

[0063] A method for manufacturing a hot-rolled wire rod, the manufacturing method of which is different from that of Example 3 in that the molten salt temperature of the rear-stage molten salt is 535° C., the processing time is 350 s, and a hot-rolled wire rod finished product is obtained after the production line is off the line.

[0064] Comparative Example 6:

[0065] A method for manufacturing a hot-rolled wire rod, the manufacturing method of which is different from that of Example 3 in that the molten salt temperature of the rear-stage molten salt is 605° C., the processing time is 700 s, and a hot-rolled wire rod finished product is obtained after the production line is off the line. Embodiment 4:

[0066] A preferred embodiment of the 2060MPa grade high-strength multiphase hot-rolled wire rod for bridge cables of the present invention, the chemical composition and mass percentage of the hot-rolled wire rod include C: 0.91%, Si: 0.82%, Mn: 0.7%, Cr: 0.42%, V: 0.035%, P: 0.012%, S: 0.015%, and the rest are Fe and unavoidable impurities; the manufacturing method thereof is manufactured according to the process flow of rolling → spinning → online molten salt semi-quenching treatment → roller slow cooling → coiling, specifically:

[0067] The rolling process is used to heat a steel billet with a specification of 220mm×220mm through a heating furnace to obtain a high-temperature steel billet that can be rolled into plasticity. The parameters of the heating furnace are controlled to promote uniform diffusion of components in the steel billet, reduce segregation, and control burning and decarburization. After the steel billet leaves the heating furnace, the steel billet is rolled into a wire with a diameter of 15mm through a rolling line. Appropriate rolling temperature and deformation are selected to improve the rolling speed and efficiency, promote dynamic recrystallization and refine grains during the final rolling process. Specifically: the heating furnace is controlled to have a soaking temperature of 1150°C. The furnace time is 100min, the initial rolling temperature is 1130℃, the final rolling temperature is 975℃, and the final rolling reduction is 34%; the wire-spinning process is used to make the wire rod out of the rolling line into a wire rod through a wire-spinning mechanism, and the wire rod is spread on the roller and transported along the roller. An appropriate wire-spinning temperature is selected to promote the wire rod to be in a high-temperature austenite state, and to avoid the formation of network carbides in the wire-spinning stage caused by too low a wire-spinning temperature, so as to form a large temperature gradient later, thereby providing favorable conditions for promoting bainite nucleation. Specifically, the wire-spinning temperature is controlled to be 935℃.

[0068] The online molten salt semi-quenching treatment process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller to pass through the first salt bath tank, i.e., the front molten salt treatment, so that the wire rod is cooled at a cooling rate of 42°C / s, and quickly passes through the network carbide precipitation interval from the high-temperature austenite state to enter the bainite phase region, inhibiting the formation of network carbides, promoting the phase transformation of part of the high-temperature austenite to bainite, and forming a structure mainly composed of bainite and untransformed austenite. The wire rod coming out of the first salt bath tank is conveyed by a roller to pass through the second salt bath tank, i.e., the rear molten salt heating isothermal treatment. The treatment promotes the transformation of untransformed high-temperature austenite into troostite structure, promotes the dispersion and precipitation of a large amount of vanadium-containing carbides, and at the same time subjects the wire rod structure to high-temperature isothermal tempering to promote the transformation of carbides into spheroidized structure and improve the strength-plasticity matching of the wire rod. Specifically: the molten salt temperature of the front-stage molten salt is 428°C, the treatment time is 16s, the molten salt circulation volume is 660t / h, and the molten salt temperature rise is ≤9°C; the molten salt temperature of the rear-stage molten salt is 578°C, the treatment time is 400s, the molten salt circulation volume is 400t / h, and the molten salt temperature rise is ≤3°C.

[0069] The roller slow cooling process uses an open insulation cover, and the wire rod that has passed through the second salt bath tank is transported by the conveyor roller into the insulation cover to prevent the wire rod from increasing stress during the cooling process, promote further toughening of the wire rod structure, and improve the softening effect of the wire rod. Specifically: the wire rod is controlled to be slowly cooled at a cooling rate of 0.45°C / s above 350°C; the coiling process is used to coil the wire rod into a coil through a coiling drum, and the hot-rolled wire rod product is obtained after packaging and storage.

[0070] Comparative Example 7:

[0071] A method for manufacturing a hot-rolled wire rod, which differs from Example 4 in that: the method is manufactured according to a process flow of rolling → spinning → online molten salt semi-quenching treatment → air cooling, wherein the air cooling is performed by opening a heat preservation cover, and conveying the wire rod through a second salt bath tank by a conveyor roller, and controlling the wire rod to be slowly cooled at a cooling rate of 1.9°C / s above 350°C, and obtaining a hot-rolled wire rod finished product after it comes off the line.

[0072] The hot rolled wire rods obtained in the above examples 1 to 4 and comparative examples 1 to 7 were subjected to microstructure and performance testing, and the comparative results obtained are shown in Table 1 below:

[0073] Table 1. Comparison of microstructure and performance of hot rolled wire rods with different compositions and manufacturing methods

[0074]

[0075] The interlamellar spacing in Table 1 refers to the interlamellar spacing of tempered troostite or troostite or tempered pearlite. It can be seen from the comparison results of Example 1 and Comparative Example 1 that compared with the C-Si-Mn-Cr-V component system, due to the combined influence of high C content and alloy strengthening, the strengthening effect is often weakened due to the uncontrollable cooling rate during the cooling phase transformation process, and at the same time, the hot-rolled wire rod is extremely sensitive to the process on the existing Stelmor air-cooling line, and it is very easy to produce abnormal structures such as high-grade network carbides and martensite, which makes it extremely difficult to carry out high-quality and stable production. The present invention combines the online molten salt semi-quenching technology to first control the rapid The cementite state skips the secondary cementite precipitation temperature interval and enters the bainite phase region, forming a structure mainly composed of bainite and untransformed austenite, and then promotes the transformation of untransformed austenite into troostite, while promoting the high-temperature isothermal treatment of the wire rod structure, which can effectively avoid the risk of abnormal structures such as network carbon and martensite produced by the C element, enhance the strengthening effect of the carbon element, and enhance the overall strength and plasticity of the wire rod. It can be seen from Examples 1 to 4 that the product can reach a tensile strength of 1470 to 1520 MPa and a cross-sectional shrinkage rate of 39 to 44%, and can be stably produced for use in the manufacture of 2060 MPa-level ultra-high strength bridge cables and other application fields.

[0076] From the comparison results of Example 1 and Comparative Example 2, it can be seen that the appropriate spinning temperature is selected to promote the austenitization of the wire rod structure and avoid the formation of network carbides due to too low spinning temperature. At the same time, it provides favorable conditions for increasing the temperature gradient and promoting the rapid transformation of the wire rod structure into bainite during the front-stage molten salt treatment. At the same time, it can also reduce the restriction on the rolling temperature, which is beneficial to improving the rolling efficiency.

[0077] From the comparison results of Example 2 and Comparative Example 3, it can be seen that the lower the molten salt temperature of the front stage molten salt and the longer the treatment time, the more austenite transforms to bainite, the proportion of tempered bainite in the wire rod increases, the strength of the wire rod increases, and the plasticity decreases. However, if the molten salt temperature is too low and the treatment time is too long, the proportion of tempered bainite in the wire rod is too small, which is not conducive to controlling the plasticity and drawing properties of the wire rod.

[0078] From the comparison results of Example 2 and Comparative Example 4, it can be seen that the higher the molten salt temperature of the front stage molten salt and the shorter the treatment time, the less the transformation of austenite to bainite, and the more the transformation of untransformed austenite to troostite, which will lead to a decrease in matrix strength and an increase in plasticity. However, if the molten salt temperature is too high and the treatment time is too short, the bainite phase transformation will be affected and the matrix strength will be lost.

[0079] From the comparison results of Example 3 and Comparative Example 5, it can be seen that the lower the molten salt temperature of the latter stage molten salt, the more beneficial it is to promote the transformation of the untransformed austenite structure to the troostite structure with finer interlamellar spacing, and the dispersion and precipitation of V-containing carbides. However, if the molten salt temperature is too low and the treatment time is too short, it is difficult to provide more thermal power for isothermal softening, which will lead to insufficient plasticity of the wire rod.

[0080] From the comparison results of Example 3 and Comparative Example 6, it can be seen that the higher the molten salt temperature of the latter stage molten salt is, the more thermal power can be provided for the isothermal softening and toughening of bainite and troostite, the transformation of carbides to spheroidization can be promoted, and the plasticity of the wire rod can be improved. However, if the molten salt temperature is too high, it will be unfavorable for the refinement of the troostite lamellae and the large-scale precipitation of V-containing carbides in the crystal. If the treatment time is too long, there is a risk of excessive loss of strength, coarsening of carbide precipitation or growth of spheroidization aggregation and loss of strength and plasticity.

[0081] From the comparison results of Example 4 and Comparative Example 7, it can be seen that the use of roller slow cooling can prevent the stress of the wire rod from increasing during the cooling process. At the same time, slow cooling can promote further toughening of the wire rod structure and improve the softening effect of the wire rod.

[0082] The series of detailed descriptions listed above are only specific descriptions of feasible embodiments of the present invention. They are not intended to limit the scope of protection of the present invention. All equivalent embodiments or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for manufacturing a 2060MPa grade high-strength multiphase hot-rolled wire rod for bridge cables, characterized in that: The manufacturing method thereof comprises: The wire rod is produced by rolling according to the chemical composition of the hot-rolled wire rod, and the chemical composition and mass percentage of the hot-rolled wire rod include: C: 0.87%~0.91%, Si: 0.70%~0.85%, Mn: 0.50%~0.70%, Cr: 0.35%~0.45%, V: 0.035%~0.045%, P≤0.015%, S≤0.015%, and the rest are Fe and unavoidable impurities; after the wire rod is spun into a wire rod at a spinning temperature of ≥915°C, it is subjected to an online molten salt semi-quenching treatment, so that the wire rod first passes through the front-stage molten salt and is cooled at a cooling rate of ≥39°C / s, and enters the bainite phase from the austenite state. zone, promoting the transformation of part of austenite to bainite, and then undergoing isothermal treatment of molten salt heating in the latter stage, promoting the transformation of untransformed austenite to bainite, promoting isothermal tempering of the wire rod structure, and finally undergoing roller slow cooling to produce a hot-rolled wire rod with a microstructure mainly composed of tempered bainite and tempered bainite, and the rest of the microspheroidized carbides forming a complex phase structure; the molten salt temperature of the front stage molten salt is 420-450°C, and the treatment time is 7-18s; the molten salt temperature of the rear stage molten salt is 550-590°C, and the treatment time is 400-600s, and the roller slow cooling controls the wire rod to be slowly cooled at a cooling rate of 0.3-0.5°C / s above 350°C.

2. The method for manufacturing 2060MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables according to claim 1, characterized in that: Before the rolling, the soaking temperature of the heating furnace is controlled to be 1100-1150° C., and the time in the furnace is 100-180 minutes.

3. The method for manufacturing 2060MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables according to claim 1, characterized in that: During the rolling, the initial rolling temperature is controlled to be 1080-1130° C., the final rolling temperature is controlled to be 935-975° C., and the final rolling reduction is controlled to be 29%-34%.

4. The method for manufacturing 2060MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables according to claim 1, characterized in that: The molten salt circulation rate of the front-stage molten salt is 560-660 t / h, and the molten salt temperature rise is ≤9°C; the molten salt circulation rate of the rear-stage molten salt is 350-450 t / h, and the molten salt temperature rise is ≤3°C.

5. A 2060MPa grade high-strength multiphase hot-rolled wire rod for bridge cables, characterized in that: The hot-rolled wire rod is manufactured by the method for manufacturing 2060MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables as described in any one of claims 1 to 4.

6. The 2060MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables according to claim 5, characterized in that: The interlamellar spacing of the tempered bainite is 70-130 mm, and the volume percentage of the tempered bainite is 55%-65%.

7. The 2060MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables according to claim 5, characterized in that: The network carbide grade of the hot-rolled wire rod is grade 0, and the mechanical property difference is ≤52MPa.

8. The 2060MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables according to claim 5, characterized in that: The hot-rolled wire rod has a diameter of 11.0-15.0 mm, a tensile strength of 1470-1520 MPa, and a cross-sectional shrinkage of 39%-44%.

Citation Information

Patent Citations

  • Heat treatment wire rod for 2060 MPa-grade bridge cable steel wires and production method

    CN112391584A

  • High-plasticity hot-rolled carbon wire rod for 1670 MPa bridge cable and manufacturing method of high-plasticity hot-rolled carbon wire rod

    CN118854174A

  • Wire rod for hot-rolled complex-phase 1770MPa-grade prestressed stranded wire and manufacturing method of wire rod

    CN118895460A

  • High-strength economical high-carbon steel wire rod and manufacturing method therefor

    WO2024213156A1